Study the Influence of Sn Dopant on the Some Structural and Optical Properties of Pure Cadmium Oxide(CdO) Thin Films - Shehab, A. A.; Mahmoud, T. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this research , pure Cadmium Oxide thin films were prepared by  thermal  evaporation Under  vacuum  method , where  pure cadmium  metal was  deposited on  glass  Substrate in Room temperature (300K) at thickness (400 Â± 30) nm with Deposition rate(1.1 Â± 0.1) nm/sec   And  then  we  oxidize a pure  cadmium  Film  in Temperature ( 350ÂºC ) for  one  hour  with existence air flow.       This  research  contained  study of   the  influence  of  doping  process  by  Tin metal (Sn) with two different  ratios (1,3) %  at  substrate temperature (473K ) on the some structural properties of pure Cadmium oxide films .       X-Ray diffraction pattern showed that all prepared films ( undoped and  Sn doped ) are polycrystalline and of cubic kind with preferred orientation along [111] plane for all doped And undoped films , and the average grain size would Decrease  with apparent shape when   The ratio of Sn  dopant  increases until  (43nm) at  ratio (3%) ,  also  this   research included a study of the influence of   Sn  dopant  with  a mentioned  ratios on the some optical properties of  pure CdO films, such as calculation of the value of optical energy gap to allow     direct   transition, and studied and calculated the absorption coefficient .       The optical investigation showed that all films prepared ( undoped  and  Sn doped) have   Absorption coefficient with a value larger than (Î± >10 4 cm-1) and this value was increased when the increase of the ratios of Sn dopant specially in the low photon energy       The optical energy gap was founded equal to (2.15 eV) for pure Cadmium   Oxide film and it  will decrease  when  the  ratio of  Sn dopant   increases  until (1.925 eV)  For  ratio (3%) .